Pre-harvest Application of ReTain (Aminoethoxyvinylglycine, AVG) Influences Pre-harvest Drop and Fruit Quality of ‘Williams’ Pears - Sinan Batur; Melike Çetinbaş (Journal of Agricultural Sciences)
‘Williams’ is the highly quality pear cultivar mostly produced in the Eğirdir region of Turkey. ReTain (15%aminoethoxyvinilglycine, AVG) is a plant growth regulator used to control pre-harvest drop and increase fruitweight and firmness. The objective of this study was to determine the responses of AVG treatments on the preharvestdrop and fruit quality of ‘Williams’ pear. Pear trees of the cultivar ‘Williams’ were sprayed 30, 21 and 7days before commercial harvest (DBH) with AVG, at doses of 100, 125 and 150 mg L-1, and assessed for pre-harvestdrop, yield, maturity, delay in harvest, fruit quality, ethylene production and respiration rate at the harvest time.Fruit samples were analyzed for fruit quality parameters which are: fruit width, fruit weight, soluble solids content(SSC), titratable acidity (TA), fruit firmness, fruit colour, fruit macro and micro elements content. Maturation ofthe 30 and 21 DBH AVG-treated fruits were delayed 3-4 days compared to the 7 DBH AVG-treated and controlgroups. The pre-harvest drop decreased with all AVG applications by approximately 38-100% in comparison withthe control group fruits. AVG treatments increased fruit size (7-10%), fruit weight (26-41%) and fruit firmness(2-16%) of ‘Williams’ pear. AVG application reduce ethylene production and respiration rate and it was found thatthe applications enhance the ethylene production and respiration rate by approximately (100%) compared to thecontrol fruits on the harvest date. Results of this study indicated that 30 DBH and 21 DBH AVG-treatments at 100mg L-1 can be recommended for ‘Williams’ pear cultivar on both pre-harvest fruit drop, as well as in harvest dateand fruit quality.